Visual narratives and Christian propaganda: an analysis of the golden glass artifacts in Late Antiquity - Campos, Ludimila Caliman (Romanitas - Revista de Estudos Grecolatinos, 2021)
This article aimed to analyse the commemorative propaganda program undertaken by Christians in Late Antiquity. For that, speeches iconographic and epigraphic readings of some decorative pieces in golden glass, with emphasis on those that refer to Pedro and Paulo. Through an interpretation of the forms of visibility the artifacts present, we seek to understand the political-religious changes that characterized Christian ekklesia in the 4th and 5th centuries, with emphasis on the apotheosis of episcopal power and ecclesiastical institutionalization.